Effect of Dwell Time and Tool Rotational Speed of Friction Stir Spot Welding on the characteristics of AA3105 joints (University of Thi-Qar Journal for Engineering Sciences, 2018)
In the last decades of the twentieth century and the first decade of this century, the issue of rationing energy and the issue of environmental conservation has become the main concern of the company's manufacturing the means of transportation. This can be achieved using Al-alloys and other light alloys as a best alternative for steel in the bodies of the auto industry. Aluminum and light metals alloys have lower melting point and so fusion welding and resistance spot welding processes cause more changes in the properties of these alloys and lead to getting unsound welding. Solid state welding methods such as friction stir spot welding consider the best alternative. In the present work, effect of dwell time and tool rotational speed on microstructural and mechanical properties of friction spot welded joints of AA3105 alloy, was investigated experimentally. The travel speed and plunging depth were kept as constant, whereas, the dwell time and rotational speed parameters were varied with different values and their effect was investigated. Lap shear test, microhardness, and metallographic tests were performed. The results showed that, the shear strength is significantly affected with variation of the input parameters. The main findings of the present work were that high shear strength of the friction stir spot welded joints is achieved at dwell time of 7.5 s and rotational speed of 1400 rpm, as well as the highest microhardness was also achieved with this set of input parameters.